Studi Kelayakan Pengembangan Potensi Wisata Di Pulau Merak Kecil - Farhatani Rahayu; Novita Putri Amanti; Tiara Utami; Arya Maranatha R. M; Alisyahaq Mahdiyatul Asdhar (Universitas Katolik Widya Karya Malang, 2023)
The potential of the Merak Kecil Island tourist attraction in Cilegon Banten is very high because it has a fascinating beach and sea landscape. This makes many tourists interested in visiting Pulau Merak Kecil. The facilities offered are also quite adequate. Anak Pulo is a local resident who manages Merak Kecil Island. Seeing and observing the great potential of Merak Kecil Island, it is necessary to develop tourism assisted by the local government. By using qualitative research methods through interviews, observation, and documentation. The data used in this research are primary data and secondary data. The results of this study are tourism potential and development shows a feasibility, so that from Aspect 4A and SWOT Analysis, Merak Kecil Island can become a competitive marine and coastal tourism.